2020
DOI: 10.4995/wrs.2020.12082
|View full text |Cite
|
Sign up to set email alerts
|

Association of Melanophilin (MLPH) gene polymorphism with coat colour in Rex rabbits

Abstract: Rex rabbit, with multiple phenotypes and colourful fur, is an interesting model for assessing the effect of coat colour gene mutations on characteristic pigmentation phenotype. Based on previous study, the <em>melanophilin</em> (<em>MLPH</em>) gene is a positional candidate gene related coat colour dilution. The fur colours are a lighter shade, e.g. grey instead of black. We sequenced 1689 base pairs of the <em>MLPH</em> gene in Chinchilla and black Rex rabbit. A total of 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Two exon skipping and a frameshift mutation within the melanophilin (MLPH) gene are associated with coat color dilution in rabbits (Lehner et al, 2013;Fontanesi et al, 2014). However, these previously reported mutations associated with coat color dilution in rabbits were not identified in the Chinchilla populations investigated here (Li et al, 2020). Moreover, the mutations in exons of the MLPH gene were detected in the DCh group ( Supplementary Table 1).…”
mentioning
confidence: 86%
“…Two exon skipping and a frameshift mutation within the melanophilin (MLPH) gene are associated with coat color dilution in rabbits (Lehner et al, 2013;Fontanesi et al, 2014). However, these previously reported mutations associated with coat color dilution in rabbits were not identified in the Chinchilla populations investigated here (Li et al, 2020). Moreover, the mutations in exons of the MLPH gene were detected in the DCh group ( Supplementary Table 1).…”
mentioning
confidence: 86%
“…In order to verify the RNA-seq results, ten pigment-related genes (Casp et al, 2002;Bhoumik et al, 2007;Mirmohammadsadegh et al, 2010;Liu et al, 2013;Hammam et al, 2014;Wang et al, 2017;Yang et al, 2018;Li et al, 2020) were selected to quantify their mRNA expression levels in the skin of two distinct color morphs of C. argus by using qRT-PCR (Figure 11). The expressions of all the selected genes of BT were extremely higher than that of AT, consistent with the results obtained through transcriptome analysis.…”
Section: Validation Of the Data Reliability By Qrt-pcrmentioning
confidence: 99%
“…Meanwhile, the MITF is an upstream TF that can directly regulate the TYR gene (Bharti et al, 2012;Raviv et al, 2014), and some genes such as SOX10, MAPK, CATs act directly or indirectly on the MITF gene to regulate the development, growth and differentiation melanocytes (Hou et al, 2000). In addition, the MLPH, CHP2, and EpoR play roles in the formation, transportation, development and other processes of pigment cells and melanoma (Bhoumik et al, 2007;Liu et al, 2013;Hammam et al, 2014;Li et al, 2020). Previous studies showed that the differential expression of albino-related genes regulated the development and differentiation of body color, and over 95 and 38 body color development related genes were found in zebrafish and Oryziaslatipes (Hidehito et al, 1994;Dooley et al, 2013).…”
Section: Validation Of the Data Reliability By Qrt-pcrmentioning
confidence: 99%
See 1 more Smart Citation